Doritos Product Marketing Innovation Based on Doritos Flat Life on TikTok Social Media to Increase Sales - Taufiq, Achmad; Hadi, Bawa Mulyono; Mau, Daniel Pandu (Transpublika Publisher, 2025)
Innovative product marketing is essential in increasing sales in today's digital age, especially through social media platforms such as TikTok. This research aims to analyse the marketing strategy used by Doritos in the campaign, as well as evaluate its impact on product sales and audience engagement. The research method used is qualitative with data collection techniques through in-depth interviews, content analysis, and consumer surveys. The results revealed that using TikTok as a marketing platform was effective in increasing brand awareness and sales. The campaign successfully created high engagement through hashtag challenges, collaboration with influencers, and organic content. A 30% increase in sales in the first month of the campaign, as well as positive engagement levels from TikTok users, showed that this marketing approach was effective. The implication of this research is the importance of understanding the audience and adapting to the dynamics of social media platforms to achieve success in digital marketing.